Predictive factors for the efficacy of Er:YAG laser treatment of urinary incontinence. (February 2020) - Erel, C. Tamer; Inan, Deniz; Mut, Aysegul
Highlights: Erb:YAG laser treatment improves the symptoms of urinary incontinence, especially stress urinary incontinence. Younger, premenopausal or early postmenopausal women with normal body mass index experience greater symptomatic improvement. The relief of symptoms is of greater duration for younger, premenopausal or early postmenopausal women with normal body mass index. Abstract: Objectives: To determine the efficacy and predictive factors for the success of Er:YAG laser treatment in patients with urinary incontinence (UI). Methods: Eighty-two patients with UI were treated by Er:YAG laser in this cohort study. The patients were evaluated by ICIQ-SF and KHQ-UI before and after the procedure. Improvement was categorized as: none (0–25%), mild (26–50%), moderate (51–75%), or high (76–100%). The duration of the treatment effect was evaluated at follow-up in relation to maximum improvement time (MIT) and total improvement time (TIT). Results: Forty-two patients were determined to have SUI and 40 patients MUI. The mean ISIQ-SF and KHQ-UI scores significantly improved after the procedure (p<0.0001). The SUI patients responded to the laser treatment significantly better (p<0.008). Younger women had significantly better results (p<0.008), while premenopausal women (p<0.032) and women in the early postmenopausal years (p<0.032) also saw a positive response to the Er:YAG laser treatment. Women with a lower BMI had greater improvement (p<0.011). The total laser energy expenditure during the sessions may also be a predictive parameter for the success of Er:YAG laser treatment of UI (p = 0.059). MIT and TIT were significantly longer among the patients in the high-improvement group. Conclusion: Er:YAG laser treatment of the symptoms of UI, especially SUI, is more efficacious and of longer duration for younger, premenopausal or early postmenopausal women with normal BMI.